Analysis of the Effect of Intake Manifold Shape on Motorcycle Engine Performance - Santoso Santoso; Reyhan Abiyyuzufar Prayitno (Widyagama University of Malang, 2022)
The intake manifold is a vehicle component where air and fuel flow from the carburetor to the combustion chamber through the intake valve. In order to get turbulent flow, it is necessary to modify the intake manifold. This research method uses data collection techniques using observation. Torque, power, fuel consumption, and exhaust emissions for each use of the intake manifold modification were tested three times at engine cycles of 2500-9000 rpm. In this study, the data were obtained from independent variables affecting dependent variation. The independent variable in this study was the shape of the intake manifold with a distance of 1 cm, 2 cm, and 3 cm. The dependent variable results from the independent variables are torque, power, fuel consumption, and exhaust emissions. It is necessary to control variables, including motorcycles according to the manufacturer specifications, testing engine performance using a 4-stroke transmission gear, engine working temperature (80-90 oC), and 92 octane fuel. 2 cm has the most significant impact on power, which is 5.47 HP. In testing the shape of the intake manifold, the threaded distance of 3 cm has the most significant impact on Torque, which is 7.15 Nm. In testing the shape of the intake manifold, which has an efficient impact on fuel consumption on a thread distance of 2 cm at 3000 rpm engine cycle with a time duration of 155.33 seconds. The peak engine cycle at 8000 rpm is the most economical on a 3 cm wine thread, with 71.67 seconds. The results of exhaust gas emissions for Hydrocarbon (HC) that are not burned out in the combustion process of the motor are the lowest, namely at a thread distance of 1 cm with an engine cycle of 2000 rpm with a result of 263.33 ppm, for engine cycle 9000 rpm with a yield of 246 ppm. For levels of Carbon Monoxide (CO), which is incomplete combustion in the process of engine performance, the lowest is at a 2 cm threaded distance at a 2000 rpm engine cycle with a result of 2.22%, and for an engine cycle of 9000 rpm with a result of 0.23%.